The teaching of the civil-military dictatorship in Maranhão: the story of Maria Aragão in comics - Moreira, Ionayra Pinto Lima (Seven Editora, 2023)
This research addresses the history of the Civil-Military Dictatorship in Maranhão, through the trajectory of the activist Maria Aragão, given the scarcity of regional histories in textbooks. The work aims to develop comics based on the history of Maria Aragão in her political life in the dictatorial context, which will be the product of the research that will have the title: Civil-military dictatorship in Maranhão: Maria Aragão and her fight. This didactic proposal is part of the dissertation project of the Graduate Program in Basic Education Teaching Management at the Federal University of Maranhão. DOI: https://doi.org/10.56238/devopinterscie-049